Design, fabrication, and performance testing of an energy storage and return (ESAR) foot prosthesis made of prepreg carbon composite - Rifky Ismail; Murti Ayu Nursafitri; Akmal Putra Fardinansyah; Deni Fajar Fitriyana; Athanasius Priharyoto Bayuseno; Januar Parlaungan Siregar; Muji Setiyo; Alfiana Fitri Istiqomah; Sulistyo Sulistyo (Mechanical Engineering for Society and Industry, 2025)
The high demand for prosthetics in Indonesia is not followed by the ability and quality of local production to fulfill the community's needs. There is a lack of comprehensive data regarding the specific challenges encountered by local prosthetic manufacturers in Indonesia, particularly in terms of technological limitations. This study aims to understand the effect of design parameters on the performance of the energy storage and return (ESAR) foot prosthesis prototype in normal walking activities for amputees. Three different designs were created according to commercial products, and a convergence test was conducted to ensure accurate results. Finite element method (FEM) analysis was used to determine the amount of deformation that occurred in each design made when applied with 824 N axial force. The ESAR foot prosthesis prototype made from carbon prepreg was fabricated using an out-of-autoclave method, and the mechanical testing was performed with a compressive test. The results indicated that the optimal design for the ESAR foot prosthesis determined by the decision matrix scoring criteria was Design 3. The final scores for Designs 1, 2, and 3 were 54, 53, and 77, respectively. Design 3 is the easiest to manufacture, has the slightest complexity, and the lightest mass, and undergoes the least deformation during simulation, although it is the least attractive. The study found a significant difference in displacement between the deflections obtained from simulation and experiment. This occurred because the prototype was found to have delamination, which decreased the load-bearing ability of the prototype during compressive testing. Compressive testing on the prototype yielded a deflection of 22.695 mm in heel strike and 18.065 mm in toe-off positions, while FEM analysis showed 16.377 mm and 3.912 mm. Therefore, strict quality control is essential, especially when using materials such as carbon prepreg, which are prone to delamination if not properly processed.